PROFIL PEMECAHAN MASALAH DALAM MENYELESAIKAN SOAL PADA MATERI PERSAMAAN GARIS LURUS OLEH SISWA KELAS VIII SMP NEGERI 9 PALU DITINJAU DARI ADVERSITY QUOTIENT (AQ) - Putri, Istifanah Maharani; Paloloang, Baharuddin; Pathuddin, Pathuddin; Lefrida, Rita (Universitas Tadulako, 2025)
The purpose of this study is to obtain a description of the problem solving of straight line equations in terms of Adversity Quotient (AQ) of SMP Negeri 9 Palu students. This type of research is descriptive qualitative research. The subjects of this study were 3 students taken from 26 students of class IX F SMP Negeri 9 Palu. Data on students' AQ level was obtained by giving ARP questionnaire, while data on students' problem solving was obtained by tests and interviews. Using Polya's steps on Climber, namely; (1) Understand the problem: students understand and realize the completeness of the information in the problem (2) Develop a plan: students explain the problem solving plan well (3) Implement the Problem: students consistently carry out according to what was previously planned (4) Recheck: students check each step of problem solving. Using Polya's steps on Camper, namely; (1) Understand the problem: students understand the problem by reading the problem repeatedly. (2) Developing a plan: students explain the problem solving plan quite well. (3) Implementing the plan: students consistently carry out according to what was previously planned. (4) Rechecking: students doubt the answers that have been obtained. Using Polya's steps on Quitters, namely; (1) Understanding the problem: students identify information from the problem. (2) Making plans: students are able to make plans (3) problem solving: students do not solve the whole problem. (4) Rechecking: students do not solve the whole problem.